Proposed Pathway for Nigerian Libraries in The Face of Prevailing Educational and Societal Requirements - Onuoha, Juliet; David-West, Boma Torukwein; Chukwueke, Chukwuemeka (Ghana Library Journal, 2023)
It is very clear that the library, regardless of the type, plays a fundamental role in the educational and societal development of any nation. The resources and services offered by these libraries create opportunities for learning, support literacy and education, and help shape the new ideas and perspectives that are central to a creative and innovative society. Sadly, most of these libraries Nigeria are highly faced with great challenges,  hence, the need to  device a pathway. This paper critically looked at the state of the Nigerian libraries in terms of  its educational and  societal requirements. However, before delving into the pathway for the Nigerians libraries  in the face of prevailing  educational and societal requirements, some of the challenges faced by these libraries  were x-rayed. The paper  concludes that much is expected of these Nigerian libraries which have strived from  the periods of less competition to  the period of high competition and expectation. in order to meet these  numerous educational and societal  requirements, there is need for a pathway, especially a joint role to be  played by the librarians, educators, and  government. One of which is the issue of a national policy and proper  funding of these libraries.